Paciente de sexo Masculino de 65 años de edad con Tumor Maligno de Próstata. - Macaquiza Chiluiza, Joseline Daniela (2021)
This present clinical case is a 65-year-old male patient, who attends a routine medical appointment to continue in treatment of presenting a personal pathological history of a malignant prostate tumor diagnosed with 1 year of evolution, chemotherapy is performed 2 times a month he still has difficulty when starting to urinate, frequent urination, severe headaches, weakness and at the moment he is without any new symptoms, does not present surgical or family history and does not have any type of allergies. A nutritional intervention is carried out in order to improve the style and quality of life of the patient according to their pathology. In anthropometric evaluation we have a weight of 41kg and a height of 150 cm which reflects a nutritional status with a BMI of 18.2kg / m2 gives a mild malnutrition according to the WHO, in the arm circumference of 14.9 cm of 60% standard deviation according to FELANPE decreased muscle mass. Regarding the biochemical evaluation, albumin values of 2.74mg / dl are evidenced, which gives hypoalbuminemia, presents slightly low urea and creatinine. The patient is prescribed a 1600kcal diet, with a soft hyper protein and hyper caloric consistency, divided into 5 times of meals of moderate volume. In conclusion, the control of the therapeutic diet plan in the patient is maintained, since through the follow-up of the assessment, the diagnosis and intervention resulted in favorable changes in terms of their weight gain, nutritional status and pathological condition.